2003
DOI: 10.1046/j.1532-5415.2003.51117.x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dementia and Midlife Risk Factors: the Radiation Effects Research Foundation Adult Health Study

Abstract: Increased SBP and low milk intake in midlife were associated with VaD detected 25 to 30 years later. Early behavioral control of the risk factors for vascular disease might reduce the risk of dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
163
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(174 citation statements)
references
References 27 publications
7
163
1
3
Order By: Relevance
“…Similarly, Yamada and colleagues found that a self-assessment of physical activity (as a continuous variable) was not associated with the risk for AD and vascular dementia in older individuals (6). In the Religious Orders Study, an estimate of hours per week spent doing physical activities was not associated with incident AD or decline in cognitive function after 4 years of follow-up, despite a similar analytic design to the one employed in the current study where physical activity was divided into quartiles (7).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Yamada and colleagues found that a self-assessment of physical activity (as a continuous variable) was not associated with the risk for AD and vascular dementia in older individuals (6). In the Religious Orders Study, an estimate of hours per week spent doing physical activities was not associated with incident AD or decline in cognitive function after 4 years of follow-up, despite a similar analytic design to the one employed in the current study where physical activity was divided into quartiles (7).…”
Section: Discussionmentioning
confidence: 96%
“…27 Given the available evidence from epidemiologic studies and RCTs, we conclude that midlife, but not late-life, hypertension is associated with an increased risk of AD and dementia. We therefore pooled results from studies of mid-life hypertension that have been included in systematic reviews [28][29][30][31][32] to calculate a weighted OR of 1.61 (95% CI: 1.16, 2.24) (Appendix 1), which was used to calculate PAR estimates for mid-life hypertension.…”
Section: Hypertensionmentioning
confidence: 99%
“…Diabetes is a known risk factor for vascular disorders, which, in turn, increase the risk of dementia [20]. Some studies suggested the mediating role of vascular diseases in the association of diabetes with impaired cognition or dementia [21,22], and other reports showed a synergistic effect of diabetes and vascular disease on dementia risk [23][24][25]. Alternatively, there are mechanisms that may link diabetes with dementia.…”
Section: Introductionmentioning
confidence: 99%